TUNJUK AJAR DALAM NASKAH SI JANGKANG (NEGARA YANG HILANG) KARYA FEDLI AZIS - Satriyanto, Bagus; ', Elmustian; ', Auzar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This is a research of moral values in the text of Si Jangkang (negara yang hilang) written by Fedli Aziz. This text contains some moral value that teach about the relation human and God, the relation between humans, and the relation of humans to themself. This research uses qualitative approach and descriptive method to describe the moral values in the text of Si Jangkang (ngara yang hilang) written by Fedli Aziz. The data are collected by applying the data colleting technique, and then, are classified based on categories of (1) Relation of human and God which involves devotion to God, simple life, and feeling of grateful to God. (2) relation between hummans which involves conformity to the parents, to theleaders, to the unity, sense of justice and righteousness, sense of planting mind and returning favor, deliberation, positive thinking, oppennes, sense of bashfulness, affectionate, and sense of forgiving and generousity. (3) Relation of human to themself which involves the virtue of oneself, sincerity and sense of willingness to sacrifice, hardworking deligence, independence and confidence, responsibility, sense of bashfulness, right and ownership, courage, honesty, thirfty and through, sense of sulking, self awareness, timewise, life simply, and visionary.Keywords: Moral value,the text Si Jangkanng